2011
DOI: 10.1007/s12194-011-0134-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of anti-scatter grids for digital imaging with use of a direct-conversion flat-panel detector

Abstract: Our purpose in this study was to establish a selection standard for anti-scatter grids for a direct conversion flat-panel detector (FPD) system. As indices for grid evaluation, we calculated the selectivity, Bucky factor, and the signal-to-noise ratio improvement factor (SIF) by measuring rates of scatter transmission, primary transmission, and total transmission (based on the digitally displayed measurement values of the FPD system), by using 4 acrylic phantoms of different thicknesses. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…It was found that if the scattered flux is cut to 10% of its actual value, the accuracy of the estimated plutonium thickness reaches the level of the result when no scattered flux is allowed on the detector (see supplementary material 29 ). This degree of reduction can be achieved with current-generation anti-scatter grids, 28 and the results suggest that these grids would need to be used when obtaining real radiographic data.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that if the scattered flux is cut to 10% of its actual value, the accuracy of the estimated plutonium thickness reaches the level of the result when no scattered flux is allowed on the detector (see supplementary material 29 ). This degree of reduction can be achieved with current-generation anti-scatter grids, 28 and the results suggest that these grids would need to be used when obtaining real radiographic data.…”
Section: Methodsmentioning
confidence: 99%
“…First, the bucky factor B, which is one of the physical characteristic values of grids, is expressed by the following equation using the total x-ray transmittance of a grid T t [21][22][23][24]:…”
Section: Derivation Of Mif G (U)mentioning
confidence: 99%
“…Various reports have been made concerning the evaluation of the grids [18][19][20][21][22][23][24]. However, in recent years, a new index called the SNR improvement factor (SIF), to which the concept of the SNR has been applied, was introduced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of an anti-scatter grid is an effective way to significantly reduce the amount of scattered radiation reaching the x-ray detector and thereby improve the image quality for diagnostic x-ray imaging (Sandborg et al, 1993;Fetterly and Schueler, 2009;Mizuta et al, 2012). However, for megavoltage (MV) x-ray imaging in radiotherapy (Herman et al 2001), the use of a MV anti-scatter grid is not practical since a MV grid would be very bulky, heavy, and costly (Watson et al, 2005;Maltz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%